ISOLATION AND MS STUDY OF FRIEDELINOL FROM THE LEAVES OF TERAP (ARTOCARPUS ODORATISSIMUS BLANCO) - ERWIN; SRI SULISTYANINGSIH; IRAWAN W.KUSUMA (International Journal of Pharma and Bio Sciences, 2015)
Artocarpus odoratissimus Blanco (local name: Terap) is one of the Artocarpus species was taken from the tropical forests of East Kalimantan. . A friedelinol (triterpene) was isolated from the leaf extracts of the plant and the compound structure was established from the FT-IR and mass spectral data and confirmed by a standard compound. The compound has moderate cytotoxicity against a brine shrimp, A. salina with LC50 48.39 ppm.